Konsep Pendidikan Anak Berkarakter Menurut Pemikiran Imam Al-Ghazali - Nurhayati Nurhayati; Hayatun Sabariah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to examine the concept of character education according to Imam Al-Ghazali, as well as its relevance in the context of education in Indonesia today. The research method used is a literature study by collecting and analysing written sources, such as books, journals, and scientific papers on Al-Ghazali's thoughts on character education. The results show that Al-Ghazali defines character education as the formation of morals through good habits instilled from an early age. He emphasised the importance of character education that is oriented towards getting closer to Allah SWT and achieving happiness in this world and the hereafter. The methods recommended by Al-Ghazali include giving examples, training, and habituation, as well as advice that has high psychological weight. The implementation of character education is expected to produce individuals with good character and spiritual toughness. In conclusion, character education initiated by Al-Ghazali can be a solution in shaping a whole person, faithful, and morally good.